Building Self-reliance: A Framework to Evaluate Smallholder Coffee Farmers’ Pursuit of Commercialization - Colby J. Silvert; John Diaz; Laura A. Warner; T. Grady Roberts; Raul Injoque (Journal of International Agricultural and Extension Education, 2021)
This study examines the application of a self-reliance framework for practitioners and evaluators to better understand the capacities and intrinsic factors impacting smallholder coffee farmers’ commercialization behaviors. We surveyed 40 smallholder coffee producers in Peru using a quantitative instrument. Data were analyzed to determine if statistical relationships exist between farmers’ self-reliance (measured via knowledge and skills, attitudes, and aspirations) and their commercialization behaviors. Findings indicate the self-reliance framework effectively illustrates relationships between farmers’ aspirations, knowledge and skills and their commercialization behaviors, while future, additional studies are needed to better measure and understand the role of commercialization-related attitudes. Practitioners can leverage the study’s findings by using a self-reliance framework to infer farmers’ likeliness to pursue sustainable commercialization practices and align their trainings and design interventions based on evaluation findings. The conceptual self-reliance framework is the first of its kind applied for smallholder coffee commercialization. The findings demonstrate that self-reliance concepts employed recently in other contexts may potentially be used similarly by extension and development facilitators.
Keywords: coffee; commercialization; external facilitator; Peru; self-reliance; smallholder